Identification and characterisation of compounds with antimycobacterial activity from the leaves of Dombeya rotundifolia Hochs - Mashilo, Matsilane Lethabo (My University, 2023)
Plants are not only an important source of medicines, but also play a significant role in drug development for the treatment of diseases such as Tuberculosis (TB). TB is a pulmonary disease that is caused by Mycobacterium tuberculosis complex. The aim of the study is to identify and characterise antimycobacterial compounds from Dombeya rotundifolia. The plant was collected from the University of Limpopo, dried and ground into fine powder. Extraction was done using different solvents that differ in polarity. The plant was screened and analysed for phytochemicals. Three major phytochemicals were quantified using reagent assays and analysed using standard curves. The antioxidant activity of the plant was determined using 2,2-Diphenyl-1- picrylhydrazyl (DPPH) and ferric reducing power assay. The antibacterial activity of the plant extracts was tested against Mycobacterium smegmatis using bioautography and serial microplate broth dilution assay. The antibiofilm activity of the plant extracts were evaluated using crystal violet assay. The anti-inflammatory activity of the plant was determined using egg albumin protein denaturation assay. The cytotoxic effects of the extracts were evaluated using 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl tetrazolium bromide (MTT) assay on THP-1 cell line. The antimycobacterial compounds were isolated and purified using bioassay-guided assay incorporated with column chromatography and preparative TLC. The isolated compounds were analysed and identified using nuclear magnetic resonance spectroscopy (NMR). The results obtained in this study showed that water was the best extractant, extracting 57.6 mg of the plant material, followed by methanol with 38.1 mg and hexane as the least extractant with 12.4 mg. In the phytochemical analysis of TLC plates, there was a separation of compounds in all the mobile systems, and a clear separation of compounds was observed in the BEA mobile system, followed by the EMW system. The plant has all major phytochemicals that are needed for drug development. The plant extracts had antioxidant activity, which was confirmed by the quantitative assays. The high inhibitory activity of the extracts was indicated by low MIC values that inhibited the bacterial growth. The butanol extract had the lowest MIC value (0.13 mg/mL). The plant extracts were able to prevent the formation of biofilm at different concentrations. The plant was proven to have anti-inflammatory properties by having a high inhibition capacity to prevent protein denaturation. The cytotoxicity results showed that the plant was toxic to the cells. The isolated antimycobacterial compounds were identified as Eicosanoic acid and Docosanoic. They have moderate activity with the MIC value of 0.25 mg/mL. The study indicated that the isolated compounds have antimycobacterial activity, which showed that the plant has a potential to treat TB or symptoms related to TB. However, further studies are needed to evaluate their toxic effects before use.
Thesis (M.Sc. (Microbiology)) -- University of Limpopo, 2023
Keywords: Compounds; Dombeya; Antibacterial activity; Dombeya; Leaves; Tuberculosis; Plant extracts